Peran Keluarga Mencegah Generasi Z Terpapar Faham Agnostik - David Aripin Wihardja; Yanto Paulus Hermanto (Sepakat : Jurnal Pastoral Kateketik, 2025)
This research aims to provide concrete solutions regarding the strategic role of parents in preventing and addressing Generation Z's tendencies toward agnostic beliefs. The issue raised in this study is the increasing exposure of Generation Z to ideologies that question the existence of God due to the influence of globalization, information technology developments, and rapidly growing secular communities. This research uses a qualitative approach with literature study methods through secondary data analysis from scientific journals and relevant books. The novelty of this research lies in emphasizing the significance of parental involvement in building children's faith resilience amid unfiltered digital information flows. The results show that the lack of active parental roles becomes a crucial factor contributing to Generation Z's openness to agnosticism. Therefore, this study presents practical guidelines for parents in nurturing and protecting their children's faith more intentionally and contextually.